Eosinophils in the skin—a red herring masking lymphoma: a case series. (October 2018) - Jaque, Alejandra; Mereniuk, Alexandra; Sade, Shachar; Lansang, Perla; Imrie, Kevin; Shear, Neil H
Eosinophilia, both peripheral and in cutaneous tissue, is not a typical finding in mycosis fungoides; in fact, when faced with a lymphoeosinophilic infiltrate, mycosis fungoides is often not part of initial differential considerations. However, eosinophilia has been described in certain subtypes of mycosis fungoides, namely, in folliculotropic mycosis fungoides. We describe three challenging cases of folliculotropic mycosis fungoides presenting with varied clinical morphologies and a dense lymphoeosinophilic infiltrate and/or severe hypereosinophilia that obscured the final diagnosis for years. Only after treatment of the eosinophilia were the underlying atypical lymphocytes more apparent on histology and a correct diagnosis made. Thus, when characteristic features of mycosis fungoides are subtle, eosinophils can act as a red herring in terms of clinico-pathologic correlation and may prevent early and accurate diagnosis of mycosis fungoides. We suggest that further studies are needed to evaluate whether treatments to reduce eosinophilia, once other causes have been excluded, may help clear the confounding reactive inflammatory infiltrate and facilitate the diagnosis of mycosis fungoides.